2020
DOI: 10.3389/fpsyg.2020.00766
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned: Forty Years of Clinical Work With Suicide Loss Survivors

Abstract: The author has been a grief therapist in private practice for almost 40 years. The largest percentage of his clients have been suicide loss survivors, and in this article, the author reflects on the "lessons learned" about how grief therapy with survivors is both the same as, and very different from, work with clients bereaved after other types of losses. After briefly reviewing some of the empirical literature about differences between suicide bereavement and grief after other modes of death, the author argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 45 publications
3
39
0
15
Order By: Relevance
“…Panellists endorsed many statements about support specifically in the context of bereavement by suicide, showing the importance for aspects of bereavement support to be tailored for suicide bereavement. This concurs with the literature stating that although grief processes after any cause of death are similar, people bereaved by suicide, as well as helping professionals working with them, tend to emphasise that there are important differences from other forms of bereavement [10,43]. Further, research shows that some grief experiences (e.g., feelings of guilt, rejection, struggles with "why" questions, and diminished social support) can be more pronounced in adolescent grief after suicide [17].…”
Section: Discussionsupporting
confidence: 84%
“…Panellists endorsed many statements about support specifically in the context of bereavement by suicide, showing the importance for aspects of bereavement support to be tailored for suicide bereavement. This concurs with the literature stating that although grief processes after any cause of death are similar, people bereaved by suicide, as well as helping professionals working with them, tend to emphasise that there are important differences from other forms of bereavement [10,43]. Further, research shows that some grief experiences (e.g., feelings of guilt, rejection, struggles with "why" questions, and diminished social support) can be more pronounced in adolescent grief after suicide [17].…”
Section: Discussionsupporting
confidence: 84%
“…Some young participants who had experienced different losses reported that in their experience a death by suicide was more impactful than other losses, which taps into a much-debated topic in the literature regarding the “uniqueness” of loss by suicide [ 15 , 62 ]. Based on findings from controlled quantitative studies, there is growing evidence that there are more commonalities than differences between different groups of bereaved people, based on cause of death, regarding major grief themes, grief processes and grief outcomes [ 8 , 9 , 63 ]. However, there is also evidence of increased risk of mental health complications and suicidal behaviour in adolescents bereaved by suicide or other external causes compared to natural deaths (e.g., [ 50 , 59 , 60 ]), a concern that was also strongly voiced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative studies cannot grasp nuances of personal experiences, and personal accounts of individuals bereaved by suicide and narratives of clinicians seem to stress features that are experienced as unique or central to the loss by suicide in adults (e.g., [ 9 , 64 ]. Similarly, qualitative studies with adolescents have reported that they experience feelings such as guilt, shame, anger, rejection, and struggles with “why” questions, features that may be more pronounced, though not unique to suicide bereavement [ 10 , 22 , 45 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such term derives from Bowlby's attachment theory, which stresses the importance of these relationships for physical and psychological survival and well-being (Bowlby, 1969(Bowlby, , 1973Cassidy and Shaver, 2016;Lahousen et al, 2019). Accordingly, grief and mourning are framed as responses to broken attachment bonds (Bowlby, 1980;Jordan, 2020).…”
Section: Introductionmentioning
confidence: 99%